1984
DOI: 10.1111/j.1399-0004.1984.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human sperm chromosome complements from a male heterozygous for a reciprocal translocation t(11;22)(q23;q11)

Abstract: A reciprocal translocation between chromosomes 11 and 22 (t(l1;22)(q23;qll)) is a site-specific translocation that is of particular interest because of the propensity for 3: 1 segregation of the chromosomes during meiosis. There have been no published reports of chromosomally unbalanced offspring born as a result of adjacent 1 or 2 meiotic segregations in a heterozygote for this translocation. This could be explained by a meiotic mechanism which produces only 3: 1 chromosomal segregations or by differential em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…, 1983) and is more likely to result in a viable pregnancy because of the least genomic imbalance (Iselius et al. , 1983; Martin, 1984). Although these authors have documented a predominance of 3 : 1 products, Anton et al.…”
Section: Discussion With Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1983) and is more likely to result in a viable pregnancy because of the least genomic imbalance (Iselius et al. , 1983; Martin, 1984). Although these authors have documented a predominance of 3 : 1 products, Anton et al.…”
Section: Discussion With Conclusionmentioning
confidence: 99%
“…Pictures show sperm, resulting from alternate, adjacent 1 and 2, 3 : 1 segregations with different signal patterns. Especially,t(11;22)(q23;q11) has been accepted to be associated with preferential 3 : 1 segregation in meiosis I cases (Fraccaro et al, 1980;Iselius et al, 1983) and is more likely to result in a viable pregnancy because of the least genomic imbalance (Iselius et al, 1983;Martin, 1984). Although these authors have documented a predominance of 3 : 1 products, Anton et al (2004) reported that no evidence of such prevalence was found by others.…”
Section: 3%mentioning
confidence: 97%
“…Using karyotype analysis of the human sperm pronucleus after hamster egg penetration, the association between the frequency of morphologically and chromosomally abnormal sperm was examined in fertile men [ 5 ], translocation carriers [ 6 - 8 ] and post-radiotherapy cancer patients [ 9 - 11 ]. This technique provides detailed information about each individual chromosome, permitting analysis of both numerical and structural abnormalities [ 12 - 14 ].…”
Section: Human Sperm Karyotype Analysismentioning
confidence: 99%
“…These correlations between sperm morphology and aneuploidy, sometimes found in ejaculated sperm, are not found after fertilization. Karyotype data from spermatozoa after penetration in hamster oocytes do not show any relationship between chromosomal abnormalities and sperm morphology in fertile men and in men carrying translocations (Amelar et al ., ; Balkan & Martin, ; Martin, ; Martin et al ., ; Sun et al ., ).…”
Section: Resultsmentioning
confidence: 99%